Olaparib, a PARP-1 inhibitor, protects retinal cells from ocular hypertension-associated oxidative damage - Yang, Yuting; Wu, Jihong; Lu, Wei; Dai, Yiqin; Zhang, Youjia; Sun, Xinghuai (Frontiers in Cell and Developmental Biology, 2022)
Glaucoma is the most common cause of irreversible blindness worldwide. Elevated intraocular pressure (IOP) and relative hypoxia in the retina stimulate the production of reactive oxygen species (ROS), which, in turn, puts the retina and optic nerve under chronic oxidative stress. Emerging evidence has shown that oxidative stress can trigger PARP-1 overactivation, mitochondrial-associated endoplasmic reticulum membrane (MAM) dysregulation, and NLRP3 activation. Oxidative damage can trigger inflammasome activation, and NLRP3 is the only inflammasome associated with MAM dysregulation. In addition, multiple transcription factors are located on the MAM. This study aimed to investigate the protective effects and underlying mechanisms of a PARP-1 inhibitor (olaparib) against chronic ocular hypertension-associated retinal cell damage. We also mimicked hypoxic stimulation of a retinal precursor cell line by exposing the cells to 0.2% O2in vitro. We discovered that chronic ocular hypertension (COH) induces oxidative damage and MAM dysregulation in the retinal ganglion cells (RGCs). The protein levels of cleaved-PARP and NLRP3 were upregulated in the retinas of the COH rats. Olaparib, a PARP-1 inhibitor, alleviated COH-induced RGC loss, retinal morphological alterations, and photopic negative response amplitude reduction. Olaparib also relieved hypoxic stimulation-induced loss of cell viability and MAM dysregulation. Additionally, some indicators of mitochondrial performance, such as reactive oxygen species accumulation, mitochondrial Ca2+ influx, and mitochondrial membrane potential collapse, decreased after olaparib treatment. Olaparib attenuated the hypoxia-induced upregulation of NLRP3 protein levels as well as the phosphorylation of ERK1/2 and histone H2A.X. These results suggest that olaparib protects RGCs from chronic intraocular pressure elevation in vivo and alleviates the abnormal MAM dysregulation and mitochondrial dysfunction caused by hypoxia in vitro. This protection may be achieved by inhibiting PARP-1 overactivation, NLRP3 upregulation, and phosphorylation of ERK1/2.